Association between atmospheric pollutants and hospital admissions in Lisbon - Cruz, A. M. J.
Ambient air pollution is recognised as one of the potential environmental risk factors causing health hazards to the exposed population, demonstrated in numerous previous studies. Several longitudinal, ecological and epidemiological studies have shown associations between outdoor levels of outdoor atmospheric pollutants and adverse health effects, especially associated with respiratory and cardiovascular hospital admissions. The aim of this work is to assess the influence of atmospheric pollutants over the hospital admissions in Lisbon, by Ordinary Least Squares Linear Regression. The pollutants (CO, NO, NO2, SO2, O3, PM10 and PM2.5) were obtained from 13 monitoring stations of the Portuguese Environmental Agency, which provide hourly observations. Hospital admission data were collected from the Central Administration of the Health System and were compiled by age: <15, 15–64, >64 years old. The study period was 2006– 2008. Results showed significant positive associations between the following: (1) the pollutants CO, NO, NO2, SO2, PM10 and PM2.5 and circulatory diseases for ages between 15 and 64 years (0.5 % hospital admissions (HA) increase with 10 μg m−3 NO increase) and above 64 years (1.0 % stroke admission increase with 10 μg m−3 NO2 increase); (2) the pollutants CO, NO, NO2, SO2, PM10 and PM2.5 and respiratory diseases for ages below 15 years (up to 1.9 % HA increase with 10 μg m−3 pollutant increase); and (3) the pollutants NO, NO2 and SO2 and respiratory diseases for ages above 64 years (1.3 % HA increase with 10 μg m−3 CO increase).